Strategi Perlawanan Senyap Petani Mandiguh terhadap Hegemoni Perhutani: The Silent Resistance Strategy of Mandiguh Farmers Against the Hegemony of Perhutani - Muhaimin Muhaimin (Fenomena, 2016)
-This research discusses the silent resistance strategy of Mandiguh farmers against the hegemony of Perhutani by cultivating crops in the forest and disregarding land claims and reforestation issues. They only use the forest land for farming purposes. The phenomenon of utilizing forest land without violence while still resisting submission and refusing to be under Perhutani's domination makes the case of Mandiguh farmers intriguing to study. Based on the research, it can be found that the farmers' resistance strategy involves several steps: adherence to Perhutani's statements, maximizing land cultivation (Madurese work ethic), planting Perhutani's hardwood seedlings in tetelan land, uprooting the seedlings whenever possible, replanting the uprooted seedlings, and informing Perhutani that the seedlings died so they can be replanted in the next rainy season. Penelitian ini membahas tentang strategi perlawanan senyap petani Mandiguh terhadap hegemoni Perhutani dengan bercocok tanam di hutan dan mengesampingkan masalah klaim lahan serta reboisasi. Mereka hanya memanfaatkan lahan hutan untuk kepentingan bercocok tanam. Fenomena pemanfaatan lahan hutan tanpa kekerasan tetapi tetap menolak patuh dan tidak mau berada di bawah dominasi Perhutani membuat kasus petani Mandiguh menarik untuk dikaji. Berdasarkan penelitian, dapat ditemukan bahwa strategi perlawanan petani dapat diketahui melalui beberapa langkah, yaitu: kepatuhan terhadap pernyataan Perhutani, mengolah lahan secara maksimal (etos Madura), menanam bibit kayu keras dari Perhutani di lahan tetelan, mencabut bibit setiap ada kesempatan, menancapkan kembali bibit kayu keras yang telah dicabut, dan menyampaikan kepada Perhutani bahwa bibit kayu keras tersebut mati sehingga dapat ditanam kembali pada musim hujan berikutnya.